Experimental Study on the Effect of Grouting Defects on Mechanical Properties of the Rebar Connected by Full-Grouted Sleeves - Fei Guo; Junhua Li; Sicong He; Chunheng Zhou (Advances in Civil Engineering)
In this article, the mechanical properties of the steel bars connected by the full-grouted sleeve with grouting defects were investigated experimentally. The study focused on two defect factors: the insufficiency of grouting material strength and the lack of grouting fullness. The HRB400 steel bar with a diameter of 20 mm and the full-grouted sleeve with the model of GTQ4J 16 were applied in the experiment. The mechanical properties of the steel bar connected by grouted sleeve under different conditions were tested under tensile load, and these mechanical parameters were compared with the standard values in the specification. The results show that both kinds of grouting defects have a significant impact on the mechanical properties of reinforcement. The tensile strength and elongation of the joint were decreased with the decrease of the strength of the grouting material. When the water-binder ratio reaches 0.14, the strength of the grouting material is 66.4 MPa, and the mechanical properties of the joint cannot meet the requirements. At the same time, the mechanical properties of the joints were also reduced with the decrease of the grouting fullness. When the grouting fullness is below 80%, the tensile strength decreased more obviously than before, and the mechanical properties cannot reach the relevant standard.